Corrigendum: Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2021)

Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Sang Wha Kim; Won Hee Hong; Se Jin Han; Jun Kwon; Heejun Ko; Sung Bin Lee; Sib Sankar Giri; Sang Guen Kim; Byung Yeop Kim; Goo Jang; Byeong Chun Lee; Dong Wan Kim; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim ® , a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species— Triakis scyllium and Triaenodon obesus . We found that intramuscular injections of 0.2 mL/kg of Ovaprim ® for male T. scyllium and T. obesus , 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium , and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female T. obesus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim ® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.